The Influence Of Self-Efficacy On Career Decision-Making In Final Year Students In Medan City - Situngkir, Ardianto; Simarmata, Nenny Ika Putri (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to evaluate the Influence of Self-Efficacy on Career Decision Making in Final Year Students in Medan City. Based on the results of research on the influence of self-efficacy on career decision making in final year students in Medan City, the following conclusions can be drawn: The results of this study indicate that there is a significant influence between self-efficacy on career decision making in final year students who are working on their thesis in Medan City with a positive correlation, which means that if the better the self-efficacy, the better the career decision making in final year students who are working on their thesis in Medan City. The categorization results show that most final year students in Medan City have self-efficacy and career decision making abilities in the medium to high category. The results of the study show a significant difference between male and female students in terms of self-efficacy and career decision making. Female students tend to have higher self-efficacy, with dominance in the medium and high categories, and show better career decision making abilities than men. This indicates that women are more confident and persistent in planning their academic and professional future. This study shows that self-efficacy has a positive influence on career decision-making, contributing 42.8%, while other factors contribute 57.2%. These results demonstrate the importance of self-efficacy in improving career decision-making.